Implementasi Prinsip Ekonomi Islam dan Implikasinya terhadap Kinerja UMKM di Kelurahan Bagan Pete Kota Jambi - PrimaArman Husada; Efni Anita; Aztyara Ismadharliani (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
This study aims to analyze the implementation of Islamic economic principles and their implications for the performance of UMKM in Bagan Pete Village, Jambi City. This study employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving UMKM actors selected using purposive sampling. The results show that UMKM actors have implemented Islamic economic principles through practices of honesty, maintaining product quality, providing good service, and avoiding actions that may harm consumers. The implementation of these principles has positively impacted business performance, including increased customer trust, better social relationships, and the sustainability and stability of the business. However, the level of theoretical understanding of Islamic economics among business actors still needs improvement.